2022
DOI: 10.1007/s40618-022-01916-1
|View full text |Cite
|
Sign up to set email alerts
|

Androgens in endometrial carcinoma: the killer or helper?

Abstract: Purpose The aim of this review is to discuss the role of androgens in the progression of endometrial carcinoma (EC) with particular focus on the different kinds of androgenic hormones, androgen receptor (AR) and intracrine androgen metabolism. Methods A comprehensive literature search within PubMed was performed. Selected publications related to androgens and EC were reviewed. Results There are different kinds of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Although there are a few contradictory reports 13 , our findings are compatible with most previous studies, indicating that AR expression is a clinical indicator of the prognosis associated with uterine endometrioid carcinoma [16][17][18] . Although these results suggest that androgen has suppressing effects on endometrial cancers, experimental validation has not been obtained 8 .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Although there are a few contradictory reports 13 , our findings are compatible with most previous studies, indicating that AR expression is a clinical indicator of the prognosis associated with uterine endometrioid carcinoma [16][17][18] . Although these results suggest that androgen has suppressing effects on endometrial cancers, experimental validation has not been obtained 8 .…”
Section: Discussionmentioning
confidence: 84%
“…Until now, the molecular biological mechanism of the androgen/AR system for the development and progression of uterine cancer has remained unclear 7 , 8 . To the best of our knowledge, this study revealed that FOXP4 is a downstream factor of the androgen/AR system in human endometrioid cancer cells for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation